2006
DOI: 10.1073/pnas.0600250103
|View full text |Cite
|
Sign up to set email alerts
|

Mouse telocentric sequences reveal a high rate of homogenization and possible role in Robertsonian translocation

Abstract: The telomere and centromere are two specialized structures of eukaryotic chromosomes that are essential for chromosome stability and segregation. These structures are usually characterized by large tracts of tandemly repeated DNA. In mouse, the two structures are often located in close proximity to form telocentric chromosomes. To date, no detailed sequence information is available across the mouse telocentric regions. The antagonistic mechanisms for the stable maintenance of the mouse telocentric karyotype an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
89
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 35 publications
10
89
1
1
Order By: Relevance
“…We found different types of centromere aberrations in U2OS ( Fig. 2A, i-iv), in line with evidence suggesting that satellite changes are driven by different mutational processes, from recombination to unequal exchange and translocation (18,28). The majority of rearrangements observed were as in Fig.…”
Section: Significancesupporting
confidence: 88%
“…We found different types of centromere aberrations in U2OS ( Fig. 2A, i-iv), in line with evidence suggesting that satellite changes are driven by different mutational processes, from recombination to unequal exchange and translocation (18,28). The majority of rearrangements observed were as in Fig.…”
Section: Significancesupporting
confidence: 88%
“…For instance, in M. musculus domesticus, the paradigmatic case of centric fusion, no telomeric sequences are retained in the biarmed chromosomes (Garagna et al 1995, Nanda et al 1995, Kalitsis et al 2006; no ITS are observed either in the biarmed chromosomes of the shrew Suncus murinus (Rogatcheva et al 2000). In other cases with a high level of Rb (Robertsonian) variation, such as in the Sorex araneus complex (Zhdanova et al 2005) and Mus minutoides (Castiglia et al 2002(Castiglia et al , 2006, the opposite situation is the rule.…”
mentioning
confidence: 99%
“…The minor and major satellite sequences are highly conserved across the centromeres of all mouse telocentric chromosomes: the minor satellite monomers share a mean pairwise identity of 95% (Kalitsis et al, 2006); the major satellite monomers share a mean deviation from the consensus sequence of 3.9% (Vissel & Choo, 1989). This high degree of sequence conservation argues strongly for frequent recombinational exchanges between nonhomologous telocentric chromosomes driving sequence homogenization at mouse centromeres (Kalitsis et al, 2006;Vissel & Choo, 1989).…”
Section: Rodentiamentioning
confidence: 96%
“…This high degree of sequence conservation argues strongly for frequent recombinational exchanges between nonhomologous telocentric chromosomes driving sequence homogenization at mouse centromeres (Kalitsis et al, 2006;Vissel & Choo, 1989).…”
Section: Rodentiamentioning
confidence: 97%